2015
DOI: 10.1016/j.mjafi.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of training in neonatal resuscitation using self inflating bag and T-piece resuscitator

Abstract: a b s t r a c tBackground: Both the self inflating bag and the T-piece resuscitator are recommended for neonatal resuscitation, but many health care workers are unfamiliar with using the latter.A prospective, comparative, observational study was done to determine the ease and effectiveness of training of health care personnel in the two devices using infant training manikins.Methods: 100 health care workers, who had no prior formal training in neonatal resuscitation, were divided into small groups and trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…Understanding the device and its potential adverse effects or limitations is critical. Mathai et al compared set up times and effectiveness of the T piece and the self-inflating bag, and found that whilst the Neopuff took longer to set up, it was more effective in delivering adequate pressures (22,23).…”
Section: Provision Of Ippvmentioning
confidence: 99%
“…Understanding the device and its potential adverse effects or limitations is critical. Mathai et al compared set up times and effectiveness of the T piece and the self-inflating bag, and found that whilst the Neopuff took longer to set up, it was more effective in delivering adequate pressures (22,23).…”
Section: Provision Of Ippvmentioning
confidence: 99%
“…In uno studio si evince che l'utilizzo di questo dispositivo per la rianimazione neonatale ha diminuito di 2/3 la mortalità e la morbilità dei neonati [13] . Per quanto riguarda la variabile legata al fattore umano, tutti e quattro gli studi che trattano questo argomento mostrano che i diversi profili professionali, infermiere e medico, nonostante evidenzino delle differenze in termini di numeri, sono parimenti efficaci [16] , essendo i volumi insufflati e la pressione di insufflazione perfettamente nei valori di riferimento [14] . Inoltre, si è studiato che la compressione del pallone non differisce affatto se vengono utilizzate 3 o 5 dita della mano o la mano completa [15] .…”
Section: Discussioneunclassified
“…L'inquadramento professionale ha evidenziato differenze sostanziali tra i diversi operatori. I fisioterapisti erogano volumi e pressioni più precise in confronto ai medici ed infermieri che a confronto si equivalgono [16] . Questa differenza si basa sul tipo di istruzione ed allenamento dell'operatore, in quanto l'istruzione dei fisioterapisti sembrerebbe essere più efficiente in confronto agli altri.…”
Section: Il Fattore Umano Nell'erogazione Della Ventilazioneunclassified